Pengaruh Tingkat Pendapatan dan Beban Tanggungan dalam Keluarga terhadap Penyediaan Fasilitas Pendidikan di Rumah - Lailatul Fitriyah; Fadila Sugi Muliawati; Hani Fuddin; Indah Suprehhati; Joice Zhenrike Memmase; Kiki Febrianti; Laily Fitriani; Hadi Soekamto; Fatiya Rosyida (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2023)
In supporting the achievement of educational goals, it is necessary to provide educational facilities at home to support learning activities. Economic conditions including the level of income and burden of dependents in the family have a role in supporting learning achievement and the need for children's educational facilities at home. The research objective was to determine the effect of income levels and family burden on the provision of educational facilities at home. The sample of this study is the community or parents who have school children in Bangil District, Pasuruan Regency with a total of 450 households as respondents. This study uses 2 types of data, namely primary data and secondary data. Primary data was obtained directly by means of surveys and interviews with the community. While secondary data was obtained through literature studies in several journals, articles, and through government data that is in accordance with this research. The method in this study is a quantitative study using ordinal logistic regression analysis. Based on the results of the analysis of variable X1 (income) has a significance value (0.624 > 0.05) meaning that partially the income variable does not affect educational facilities. Likewise, the X2 variable (Depends) has a significance value (0.231 > 0.05) meaning that partially the dependent variable does not affect educational facilities.